AFFECTING MATHEMATICS SUCCESS THROUGH REVIEW ANALYSIS FACTORS - Kumar, Vinod; Tuteja, Amit (International Journal of Psychosocial Rehabilitation, 2021)
One of the major issues and concerns of instructors has been the nature of instructing and learning science. Understanding the factors that influence arithmetic performance is especially important when deciding on the optimal structure options. Through the collection of audits, this article was created to determine the factors that influence understudy math achievement. The three most powerful aspects that should be addressed in plan choices were instructional methods and tactics, instructor expertise in math training, and inspiration or fixation, according to the findings.